2009
DOI: 10.1056/nejmoa0808431
|View full text |Cite|
|
Sign up to set email alerts
|

Glucose Control and Vascular Complications in Veterans with Type 2 Diabetes

Abstract: Intensive glucose control in patients with poorly controlled type 2 diabetes had no significant effect on the rates of major cardiovascular events, death, or microvascular complications with the exception of progression of albuminuria (P = 0.01) [added]. (ClinicalTrials.gov number, NCT00032487.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

63
2,450
6
172

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 4,274 publications
(2,753 citation statements)
references
References 23 publications
63
2,450
6
172
Order By: Relevance
“…Moreover, glycaemic goals were more often achieved by patients in the older subgroups regardless the presence of a CVD, in accordance with the results from clinical trials and observational studies suggesting that a global control of cardiovascular risk factors in older patients provides a greater benefit regarding morbidity and mortality than an intensive glycaemic control 13, 14, 15, 16, 17. Antihypertensive treatment, for instance, has benefits even in very old patients 18, 19, 20, 21, and there are also compelling evidences of the benefit of statins and antiplatelet agents in older adults in secondary prevention of CVD, while its use in primary prevention is controversial, and individual characteristics and the risk of related adverse events should be taken into account 5, 7, 22, 23, 24, 25.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, glycaemic goals were more often achieved by patients in the older subgroups regardless the presence of a CVD, in accordance with the results from clinical trials and observational studies suggesting that a global control of cardiovascular risk factors in older patients provides a greater benefit regarding morbidity and mortality than an intensive glycaemic control 13, 14, 15, 16, 17. Antihypertensive treatment, for instance, has benefits even in very old patients 18, 19, 20, 21, and there are also compelling evidences of the benefit of statins and antiplatelet agents in older adults in secondary prevention of CVD, while its use in primary prevention is controversial, and individual characteristics and the risk of related adverse events should be taken into account 5, 7, 22, 23, 24, 25.…”
Section: Discussionsupporting
confidence: 84%
“…In the ADVANCE and Veterans Affairs Diabetes Trial, however, tight glycemic control did not lead to an improvement in cardiovascular outcomes, whereas in the ACCORD trial, in which patients had underlying cardiovascular disease, intensive treatment was associated with higher cardiovascular mortality risk 29, 30, 31. Findings from these recent studies have collectively raised the question of whether glycemic control in populations with an underlying cardiovascular risk may do more harm than good, which is particularly applicable to patients on hemodialysis in whom the risks of cardiovascular morbidity and mortality are high.…”
Section: Discussionmentioning
confidence: 95%
“…Ford reported that compared with a two years period (1999–2000), the estimated 10‐year risk for developing coronary artery disease among people with diagnosed diabetes was 22% lower by 2007–2008 5. This improved risk factor control may be one reason explaining the failure of more aggressive hypoglycemic drugs to reduce macrovascular disease in diabetes 12, 13. Whether this improvement in CHD as a result of risk factor control translates to a reduction in mortality after revascularization has not previously been reported and our observational study provides data from a large cohort suggesting this may be the case and provides stimulus for further research.…”
Section: Discussionmentioning
confidence: 99%